The U.Porto Open Repository: The Role of the Information System - Eugénia Matos Fernandes (2010)
The creation and the dissemination of knowledge are nuclear to the mission of universities. As JohnNewman anticipated in his work "The Idea of a University"1] Knowledge is capable of being its own end.We all know and experiment the influence of the new information and communication technologies (ICT)in our daily work and in the way we live in society. These technologies are having a tremendous impacton production and diffusion of knowledge. The open access movement for scholarly communicationbears on the possibilities of Internet technologies, and institutional repositories on the Web are seen asnew ways to support that primary constituent of the universities' mission.In this work we will present the institutional repository of the University of Porto (U.PORTO) from itscreation to the present moment, emphasizing its goals and the key factors that influenced most theadhesion of the academic community to self-archiving, allowing that from November 2007, when therepository was created, to present days the number of publications registered increased by an order ofmagnitude, the University of Porto now being the higher education institution in Portugal that offersmore open access full text publications, over 11.000 documents. To achieve these results, theconnection between the U.PORTO Information System, SIGARRA, to the DSPACE platform, that supportsthe University repository was decisive, and we will address its implications as well as the main directionsfor future developments.